The Intricate Link among Gut “Immunological Niche,” Microbiota, and Xenobiotics in Intestinal Pathology - Pagliari, Danilo; Gambassi, Giovanni; Piccirillo, Ciriaco A.; Cianci, Rossella (Mediators of Inflammation, 2017)
Inflammatory bowel diseases (IBDs) are diseases characterized by various degrees of inflammation involving the gastrointestinal tract. Ulcerative colitis and Crohn’s disease are characterized by a dysregulated immune response leading to structural gut alterations in genetically predisposed individuals. Diverticular disease is characterized by abnormal immune response to normal gut microbiota. IBDs are linked to a lack of physiological tolerance of the mucosal immune system to resident gut microbiota and pathogens. The disruption of immune tolerance involves inflammatory pathways characterized by an unbalance between the anti-inflammatory regulatory T cells and the proinflammatory Th1/Th17 cells. The interaction among T cell subpopulations and their related cytokines, mediators of inflammation, gut microbiota, and the intestinal mucosa constitute the gut “immunological niche.” Several evidences have shown that xenobiotics, such as rifaximin, can positively modulate the inflammatory pathways at the site of gut immunological niche, acting as anti-inflammatory agents. Xenobiotics may interfere with components of the immunological niche, leading to activation of anti-inflammatory pathways and inhibition of several mediators of inflammation. In summary, xenobiotics may reduce disease-related gut mucosal alterations and clinical symptoms. Studying the complex interplay between gut immunological niche and xenobiotics will certainly open new horizons in the knowledge and therapy of intestinal pathologies.